A retrospective cost analysis of the frequency and cost of transfusion premedications. Issue 8 (9th April 2019) - Christensen, Bradley W.; Rubinstein, Samuel M.; Bastakoty, Dikshya; Savani, Bipin N.; Booth, Garrett S.
Abstract : BACKGROUND: Acetaminophen and diphenhydramine are routinely administered to prevent febrile non‐hemolytic and allergic blood transfusion reactions despite multiple randomized controlled trials demonstrating that this practice lacks efficacy. As a result, patients are exposed to the adverse effects of these medications and their financial burdens with no expected benefit. The aim of this study was to quantify the frequency and cost of transfusion premedications in patients with acute myeloid leukemia (AML). STUDY DESIGN AND METHODS: This was a retrospective study of patients with AML admitted to Vanderbilt University Medical Center (VUMC) for induction chemotherapy between January 2008 and December 2016. Data were collected on the number of platelet and packed red blood cell (PRBC) transfusions each patient received during the initial inpatient encounter for AML, as well as on the administration of premedications prior to each transfusion. RESULTS: During the 9‐year study period, 948 AML patients received a total of 19, 820 transfusions. Of these, 30% were preceded by oral diphenhydramine, 8% by intravenous diphenhydramine, and 39% by oral acetaminophen. The percentage of patients that received a transfusion preceded by a premedication increased over the study period (p = 0.03), as did the percentage of transfusions preceded by a premedication (p = 0.02). The total unadjusted cost of pre‐transfusion medications to the institution during the study period was $50, 309.77, or $52.67 per patient with AML. The cost of premedications per patient did not increase over the study period (p = .45). CONCLUSIONS: Routine transfusion premedication administration is common in AML patients and not well‐supported by available evidence.